Analisis Motivasi Latihan Atlet Rugby 7s Putri di Masa Pandemi Covid-19: Analisis Motivasi Latihan Atlet Rugby 7s Putri di Masa Pandemi Covid-19 - Solikah, Nur Luthfiatus; Satrio Utomo, Rizki; Priambodo, Anung; Hanania, Rida; Widyah Kusnanik, Nining; Hidayat, Taufiq; Wibowo, Sapto (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
This study is designed to determine the level of motivation rugby 7s athletes in Indonesia after the covid-19 pandemic. The research method used is a survey method with a quantitative descriptive type of research. Participants in this study included 76 female rugby 7s athletes (average athlete age = 19 ± 3.66 years, min = 13 years, max = 27 years, average height = 157.9 ± 6.45 cm, average weight = 54.6 ± 10.24 kg, training experience = 2.1 ± 1.72 years). The instrument used is a google form as a training motivation questionnaire that is distributed to all rugby 7s athletes throughout Indonesia. The results of this study showed the level of motivation of female rugby 7s athletes in Indonesia with results of 2.6% of athletes in the very high category, 11.8% of athletes in the high category, 48.7% of athletes in the medium category, 30.3% of athletes in the low category, and 6.6% of athletes in the very low category. There was a decrease in training intensity by 36.6%, a decrease in exercise frequency by 42.1%, and a decrease in exercise duration by 30.3%. These findings provide initial support as a benchmark in determining the training program that will be designed for the next target event so that it can contribute to increasing the motivation of 7s rugby athletes in Indonesia. Keywords: motivation, rugby sevens, covid-19, women rugby